GE_GERICHTE P/24281/2018 vom 6. Februar 2020 - GE Cour de justice (2020)
DROIT D'ÊTRE ENTENDU;PROLONGATION DU DÉLAI;COMPÉTENCE RATIONE LOCI;INFRACTIONS CONTRE L'HONNEUR | Cst.29.al2; CPP.89; CPP.310; CP.3; CP.8; CP.173; CP.174